Study of Perceptions and Obstacles from Postgraduate Education Students About Scientific Publication as a Graduation Requirement - Utama Alan Deta; Husni Mubarak; Yetty Septiani Mustar; Ahmad Wachidul Kohar; Muhammad Abdul Ghofur (International Journal of Current Educational Research, 2022)
The Cooperation, Publication and Internationalization Group was formed as a postgraduate support unit at the Universitas Negeri Surabaya to assist students in the process of producing and publishing scientific publications. In order to provide assistance and facilitation in writing scientific articles for Unesa Postgraduate Education students, it is necessary to analyze the perceptions and obstacles faced by students in writing scientific manuscripts. The purpose of this research is to find out the perceptions and obstacles faced by Postgraduate Education students at Unesa in writing a scientific manuscript as a graduation requirement. The research was carried out qualitatively by using questionnaires, observations, and interviews with the research target of Unesa Postgraduate Educationstudentst who attended workshops and scientific manuscript assistance by the Cooperation, Publication and Internationalization Group (CPI) in Odd Semester 2022/2023. The data will be analyzed using data triangulation. Based on the results of the analysis, some students feel the need to write scientific manuscripts as a graduation requirement because it is to train student skills, improve quality, and participate in the development of innovation in science and technology. Obstacles faced by students in writing scientific articles include difficulties in determining research topics, using English in writing manuscripts, also in choosing good and reliable journals.